Uso da adubação foliar nitrogenada e potássica no algodoeiro - De Carvalho, Marco Antonio Camillo [UNESP]; Paulino, Helder Barbosa [UNESP]; Furlani-Júnior, Enes [UNESP]; Buzetti, Salatiér [UNESP]; De Sá, Marco Eustáquio [UNESP]; De Athayde, Manoel Luiz Ferreira [UNESP] (FapUNIFESP (SciELO), 2001)
The present work was conducted in Selvíria county (MS-Brazil), in the agricultural year of 1998/99, for evaluating nitrogen and potassium foliar application to supplement sowing fertilization on cotton (IAC 22) crop. A randomized complete block design with 13 treatments and four replications was used. The treatments were constituted by a control (without foliar application) and nitrogen and/or potassium foliar applications two, four, six or eight weeks after beginning of flowering. The urea was used as source of N and potassium chloride as source of K. Urea in the concentration of 10% and potassium chloride at 4% were applied at a rate of 250 L.ha-1. Height of plants, nodule number, number of reproductive branches, boll per plant, 30 boll mass, yield and fiber percentage were evaluated. It is concluded that the N doses increased the yield and decreased the fiber percentage. There was no evaluated response to the application of K or NK.
Nitrogen and potassium in foliar application on cotton crop
Keywords: Cotton; Foliar application; Nitrogen; Potassium; cotton; fertilizer application; nitrogen; potassium; Brazil; Gossypium hirsutum